1978
DOI: 10.1111/j.1476-5381.1978.tb08643.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Narcotic Analgesics on the Uptake and Release of 5‐hydroxytryptamine in Rat Synaptosomal Preparations

Abstract: 1 The effects of various narcotic analgesics on the uptake and release of labelled 5-hydroxytryptamine (5-HT) in brain and spinal cord synaptosomes were investigated.2 Methadone was most active in inhibiting 5-HT uptake (IC50 2.5 x 10-M). Levorphanol also inhibited 5-HT uptake to a large extent (IC5o 8.8 x 10-7 M) while dextrorphan, pethidine and pentazocine showed much less activity. Etorphine and morphine had virtually no such activity, with IC50s higher than 10-' and 1O-M respectively.3 The same order of po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
5
0

Year Published

1979
1979
1994
1994

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(6 citation statements)
references
References 37 publications
1
5
0
Order By: Relevance
“…Morphine perfusion into the site of 5-HT nerve terminals in the diencephalon had no effect on extracellular 5-HT or 5-HIAA . This is consistent with other reports that morphine did not enhance 5-HT release from synaptosomes or brain slices lacking 5-HT cell bodies (Mennini et al, 1978 ;Bineau-Thurotte et al, 1984;Monroe et al ., 1986) . We were unable to test higher morphine concentrations because of difficulties in separating 5-HT from the very large chromatography peak produced by 100 /tM morphine .…”
supporting
confidence: 94%
See 1 more Smart Citation
“…Morphine perfusion into the site of 5-HT nerve terminals in the diencephalon had no effect on extracellular 5-HT or 5-HIAA . This is consistent with other reports that morphine did not enhance 5-HT release from synaptosomes or brain slices lacking 5-HT cell bodies (Mennini et al, 1978 ;Bineau-Thurotte et al, 1984;Monroe et al ., 1986) . We were unable to test higher morphine concentrations because of difficulties in separating 5-HT from the very large chromatography peak produced by 100 /tM morphine .…”
supporting
confidence: 94%
“…The site where opioids act to enhance 5-HT turnover and release is a second unresolved issue. In vitro studies found no effect of morphine on 5-HT released from synaptosomes or brain slices (Mennini et al ., 1978) . This suggests that morphine does not act directly on 5-HT nerve terminals .…”
mentioning
confidence: 99%
“…Data were calculated as % of radioactivity in each sample over total radioactivity present at the beginning of superfusion. More detailed information about the methods used in studies of monamine uptake and release is given elsewhere (Mennini et al, 1978;1981) (Table 2). However, in superfusion experiments, a tendency to Table 4 shows that chronic amineptine treatment significantly reduced the maximum number of binding sites for [3H]-spiperone in striatum, as well as those for and a2-and a-NA ligands in rat cortex.…”
Section: Binding Assaysmentioning
confidence: 99%
“…[3H]5-HT accumula-in accumulation studies does not seem to play an important role for d-F, suggesting that release from the granular pool and true uptake inhibition are two different mechanisms by which d-F affects serotonin neurons in vitro. tion and [$HH]S-HT release were determined as described by Mennini et al (1978;1981b) in synaptosomes obtained from whole brains, excluding cerebellum, of normal rats or rats treated 24 h before the experiment with reserpine (10 mg/kg i.p.). [3H]5-HT (NEN, S.A. 30 Ci/mmol) was used, at a final concentration of 0.1 p M .…”
mentioning
confidence: 99%
“…The reaction was stopped by rapid filtration under vacuum through Sartorius membrane filters (0.65 pm). SeeMennini et al (1978) for details. IC," are means of 4-6 separate experiments, calculated from log-dose effect plots of 3 -4 drug concentrations.…”
mentioning
confidence: 99%